(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: The Hall technique is one of the methods used nowadays for sealing in caries in primary molars. The Hall technique using preformed metal crowns (PMCs) was first introduced in the literature in 2006 by Dr. Norna Hall, a general dentist from Scotland. Using the Hall technique, the crown is placed without local anesthesia, caries removal, or tooth preparation. An appropriate size of PMC should be chosen and filled with glass ionomer cement. Then, the crown is fitted over the carious primary molar by either the dentist’s finger pressure, or the child’s biting force. Objectives: The primary objective was to assess the knowledge, Attitude and Behavior about Hall technique among dental practitioners globally. Methods: A cross-sectional survey that was designed and developed by the authors and validated via 5 consultants in the field of pediatric dentistry. The survey instrument was a self-administered anonymous electronically generated questionnaire in English format, including demographic features such as age, gender, and specialty. It is divided into three sections regarding the HT in pediatric dentistry, including dental professionals’ Knowledge of the technique definition, advantages, onset/level of practice/training, and any concerns. Results: the total sample size of 405 dental practitioners were surveyed, most individuals scored at low levels of knowledge and awareness (59.3%), followed by those at moderate levels (33.3%), with a smaller percentage achieving high levels (7.4%). However, the behavior score about hall technique revealed that the majority, constituting 66.7%, exhibited a low behavior level in implementing the hall technique. In contrast, only 29.6% of the respondents were categorized under the good behavior level, and a mere 3.7% fell under the fair level category. Concerning their attitude score about hall technique, a significant majority of the respondents displayed a less proficient attitude, constituting 59.3% another 18.5% considered proficient and 22.2% at a fair level. Conclusion: In conclusion, this research article highlighted a significant gap in knowledge, attitude, and behavior among dental practitioners globally regarding the Hall technique for managing caries in primary molars. The majority of surveyed practitioners demonstrated low levels of knowledge and awareness, along with suboptimal behavior and attitude towards implementing the Hall technique. The findings suggest a need for increased education and training to enhance the adoption of this minimally invasive approach in pediatric dentistry.